PERAN GURU PAI DALAM MENGEMBANGKAN KECERDAS AN EMOSIONAL DAN SPIRITUAL SISWA DI SMP WAHID HASYIM DINOYO MALANG - Alfin Maulana Ramadhan; Anwar Sa’dullah; Qurroti A’yun (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The purpose of this study was to determine how the emotional and spiritual intelligence of students, how the teacher's role in developing students' emotional and spiritual intelligence and supporting factors and inhibiting factors in developing emotional and spiritual intelligence of students at Wahid Hasyim Dinoyo Junior High School Malang. This type of research uses qualitative research methods and case study research types, so that the data collection uses observation, interviews, and documentation to related parties in the research. The data analysis used is through three aspects, namely data reduction, data presentation, and drawing conclusions. The results of the study show that teachers were able to develop students' emotional and spiritual intelligence, not only providing material, PAI teachers also provided exemplary learning, guiding students to always follow activities at school such as praying dhuha in congregation, reading Surah Yasiin and so on.